Peran Desain Interior Dalam Menunjang Kenyamanan Belajar Anak Di Raudhatul Bi Al-Nazhar - Armanila Armanila; Elfidayati Elfidayati; Alya Zahro Azhari; Devi Sinta; Syariah Hafizhoh (UIN Sultan Maulana Hasanudin Banten, 2022)
The interior design describes one of the interior planning systems that functions to stay away from the state of the area by producing an atmosphere and image that fulfills the comfort, safety, and physical and spiritual needs of its users, without neglecting the aesthetic aspects of the area. Layout planning and interior design of the building. This research was attempted to identify the position of Raudahatul Athfal Bi Al-Nazhar in the interior design which is very meaningful because a good and attractive spatial layout can be more enthusiastic, not only providing comfort for children in learning and learning. So that all aspects of children's growth can grow better. This research uses qualitative research. The results of this research show that the condition of the study room will affect the quality of education. An unorganized space will definitely make children lose motivation to learn. beautiful, and also organized, integrated with the theme of learning, will definitely facilitate the learning of teachers and children. Not only that, a good classroom presses children to be more active in every learning activity.